Health related quality of life in children with autism spectrum disorder in Bangladesh - Safa, Farhana; Islam, Md Nazrul (IMC Journal of Medical Science, 2017)
Background and objective: Autism spectrum disorder (ASD) is considered as an emerging problem in our socioeconomic context. The objectives of this study were to compare the health related quality of life of children with autism spectrum disorder to that of typically developing peers. Methods: A cross sectional comparative study was conducted on autistic children and normal children in six centers of Dhaka city to see the health related quality of life from parents perspective by using the Pediatric Quality of Life Inventory 4.0 Generic Core Scales (PedsQL scale). Total of 115 children within the age group of 8-12 years were selected, among them 57 were autistic and 58 were normal peers. Results: Children with autism spectrum disorder had poor physical (mean score 6.04), emotional (mean score 9.77) and social (mean score 14.51) functions as well as learning ability (mean score 8.12) whereas normal childrens functioning mean scores were 0.10, 1.79, 0.0 and 0.45 in respective domains and the differences were significant (p<.0001) in each aspect of quality of life. Conclusion: This study revealed that, children with autism spectrum disorder experienced poorer health-related quality of life than normal children and thus the findings would contribute in implementing different strategies for improving the health status of autistic children. IMC J Med Sci 2017; 11(2): 40-44